2010
DOI: 10.1590/s0101-31222010000100012
|View full text |Cite
|
Sign up to set email alerts
|

Relações entre tratamento térmico, germinação, vigor e sanidade de sementes de tomate

Abstract: Termos para indexação: tratamento de sementes; potencial fisiológico; patologia; Lycopersicon esculentum Mill. RELATIONSHIPS BETWEEN THERMAL TREATMENT, GERMINATION, VIGOR AND HEALTH OF TOMATO SEEDSABSTRACT -Thermal treatment presents great potential on the alternative control of seed pathogens. However, there are few studies on this technology and, particularly, on its effect on the performance of seeds, especially vegetable seeds. This research aimed to study the relation of thermal treatment to the physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 5 publications
(2 reference statements)
2
9
0
5
Order By: Relevance
“…Coutinho et al (2007) found that increasing the time of heat treatment decreased the percentage of normal seedlings, resulting finally in the complete loss of germination capacity, at 60 °C for 20 minutes, in maize seeds. Braga et al (2010) concluded that heat treatment (55 °C for 30 min) is a sound option in the control of the fungi Rhizopus sp., Aspergillus sp. and Cladosporium sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coutinho et al (2007) found that increasing the time of heat treatment decreased the percentage of normal seedlings, resulting finally in the complete loss of germination capacity, at 60 °C for 20 minutes, in maize seeds. Braga et al (2010) concluded that heat treatment (55 °C for 30 min) is a sound option in the control of the fungi Rhizopus sp., Aspergillus sp. and Cladosporium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Vesicatoria in tomato seeds (SILVA et al, 2002) and Fusarium verticillioides in maize seeds (COUTINHO et al, 2007). Thermotherapy has also considerably reduced fungi that contaminate the seed surface thereby increasing their vigour (MUNIZ, 2001) and power of germination (BRAGA et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Assim, a falta de produtos ditos como seguros e que proporcionem eficiente ação no tratamento de sementes contra patógenos, torna a termoterapia um procedimento com grande potencial para minimizar ou erradicar esse problema (BRAGA et al, 2010), sendo necessário a realização de estudos mais aprofundados em relação a este tratamento.…”
Section: [223]unclassified
“…Assim, a falta de produtos ditos como seguros e que proporcionem eficiente ação no tratamento de sementes contra patógenos, torna a termoterapia um procedimento com grande potencial para minimizar ou erradicar esse problema (BRAGA et al, 2010), sendo necessário a realização de estudos mais aprofundados em relação a este tratamento. O delineamento experimental utilizado foi inteiramente ao acaso com oito tratamentos mais a testemunha e quatro repetições para cada teste.…”
Section: Fundamentação Teóricaunclassified